Tracer study on the graduates of the BSBA programs an input to curricular development - Orejana, Anne Jalandoni (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2010)
The alumni are considered as the best evidence of a program’s effectiveness in terms of employment and positions held. Moreover, they are a good source of feedback regarding the program’s relevance in the current labor market. This study was conducted to determine the employability of the graduates of the BSBA programs. The study further aimed to gather inputs about the BSBA program that could be used to improve its quality education. The study used the descriptive research design. There respondents were BSBA graduates from 2002 – 2006 identified using the snowballing technique. A structured, non-disguised questionnaire was used to gather data. Data collected were subjected to basic descriptive statistical tools such as frequency, percentage, proportions, and mean. Findings of the study indicate that 91% of the respondents are employed, with 20% holding supervisory positions and 4% holding managerial positions. Content or topics covered by the programs is found to be the main strength in the aspect of curriculum as supported by 45% of the respondents while lack of applications and exposure came out as the main weakness as indicated by 29% of the respondents. Correspondingly, the primary recommendation was to have more exposures and applications as expressed by 45% of the respondents.